The influence of the paradoxes on the development of a mathematical results - Maliaukienė, Livija (Lietuvos matematikos rinkinys, 2003)
In the paper the influence of the paradoxes on the development of a mathematical rezults from the historic standpoint is investigated, including especial importance rezults in the sphere of the provability of the consistency the Peano's arithmetic.